People in early stages of Parkinson's disease are able to intentionally reweight the use of visual information for postural control - Cruz, Caio F.; Genoves, Giovanna G.; Dona, Flavia; Ferraz, Henrique B.; Barela, Jose A. [UNESP] (Peerj Inc, 2020)
Background: Parkinson's disease (PD) leads to several changes in motor control, many of them related to informational or cognitive overload. The aim of this study was to investigate the influence of knowledge and intention on the postural control performance and on the coupling between visual information and body sway in people with and without PD standing upright. Methods: Participants were 21 people with PD (62.1 +/- 7.2 years), stages 1 and 2 (Hoehn & Yahr scale), under dopaminergic medication, and 21 people in the control group (62.3 +/- 7.1 years). Participants stood upright inside a moving room, performing seven trials of 60 s. In the first trial, the room remained motionless. In the others, the room oscillated at 0.2 Hz in the anterior-posterior direction: in the first block of three trials, the participants were not informed about the visual manipulation; in the second block of three trials, participants were informed about the room movement and asked to resist the visual influence. An OPTOTRAK system recorded the moving room displacement and the participants' sway. The variables mean sway amplitude (MSA), coherence and gain were calculated. Results: With no visual manipulation, no difference occurred between groups for MSA. Under visual manipulation conditions, people with PD presented higher MSA than control, and both groups reduced the sway magnitude in the resisting condition. Control group reduced sway magnitude by 6.1%, while PD group reduced by 11.5%. No difference was found between groups and between conditions for the coupling strength (coherence). For the coupling structure (gain), there was no group difference, but both groups showed reduced gain in the resisting condition. Control group reduced gain by 12.0%, while PD group reduced by 9.3%. Conclusions: People with PD, under visual manipulation, were more influenced than controls, but they presented the same coupling structure between visual information and body sway as controls. People in early stages of PD are able to intentionally alter the influence of visual information.
Keywords: Sensorimotor coupling; Vision; Moving room; Posture; Motor control; Parkinson's disease; Intention; Consciousness; Optic flow; Attention